Model Prediksi Jaringan Saraf Tiruan Pada Anggaran Inventaris Di Pemerintahan Kota Pematang Siantar - Tatahardinata, Jaya; Okprana, Harly; Winanjaya, Riki (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Inventory is the process of managing the procurement or inventory of goods owned by an office or company in carrying out its operational activities. Without an inventory a business activity will not be carried out, the existence of an inventory is very important. Office inventory is very important for the continuity of an agency. If one or more equipment is disturbed, it will definitely hinder the running of the company's economy which is usually in the form of irregular office inventory organization or lack of a system for inventorying office equipment. Therefore, the Neural Network is a powerful data model that is able to capture and represent complex Input-Output relationships, because of its ability to solve several problems, it is relatively easy to use, robustness of data input speed for execution, and initialization of complex systems. The method used in this research is the Backpropagation algorithm, which is a supervised method, with the help of the MATLAB application with Fletcher-reeves parameters. The research data used is Goods Identity Card data for 2018-2021. Based on this data, a network architecture model will be determined, including 1-10-1, 1-15-1, 1-20-1, and 1-30-1. From the five models, training and testing were carried out first and then obtained the results that the best architectural model was 1-10-1 with 0.01397196. So it can be concluded that the model can be used to predict inventory budget data, especially in Pematangsiantar City.